SPATIAL PATTERN AND PERCEPTION OF URINARY SCHISTOSOMIASIS (schistosoma haematobium) IN CROSS RIVER STATE, NIGERIA (2017)
Schistosomiasis is one of the prevalent Neglected Tropical Diseases (NTDs) in Cross River State, Nigeria. Its transmission is associated with bathing, swimming and swamp farming especially in endemic communities. Previous studies on prevalence have focused on parasitological detection of infected persons and the effects of environmental and socioeconomic factors on exposure to schistosomiasis. However, spatial variations in the prevalence of the disease in endemic communities have received limited attention in the literature. This study, therefore, analysed variations in schistosomiasis prevalence and the perception of water related activities on its prevalence in Cross River State, Nigeria. Disease ecology, health belief model and the triangle of human ecology of disease provided the framework, while survey design was adopted. Prevalence data were collected from National Bureau of Statistics for the period of 1981 to 2004 and Cross River State Ministry of Health 2012 schistosomiasis survey. A structured questionnaire was purposively administered on 800 selected household heads in seven endemic communities across the three senatorial districts. Data were collected on water related activities: swimming, fetching of water, bathing, laundry, sand mining, fishing, defecation in water, snail collection and farming in swampy areas; perception of blood in urine, infection, cause, modes of transmission, ailments, prevention and treatment. Endemic situations were classified into hyper >30% and meso>20% following the World Health Organisation standard. Descriptive statistics, Linear regression, Logistic regression, Correlation and Analysis of variance were used for data analyses at p<0.05. A total of 499,143 cases were reported, but the number decreased by 56.4% from 1981 to 1990 and by 33.32% between 1991 and 2004. This implied a significant decline in schistosomiasis prevalence. The disease was hyper-endemic in the north (61.0%) and central (53.7%) districts, while meso-endemic in the south district (22.1%). About 39.0% of the infected individuals were age below 20 years, while prevalence was highest in males (61.2%). Bathing (79.8%), swimming (78.2%), fetching of water (76.1%), swamp farming activities (74.7%), laundry (69.3%), snail collection (65.0%), fishing (59.8%), defecation in water (47.0%), and sand mining (38.8%) influenced prevalence of schistosomiasis. Swamp farming activities significantly influenced schistosomiasis prevalence (Odd ratio: 1.581), while a positive relationship was observed between prevalence of schistosomiasis and population size (r=0.92). Awareness of schistosomiasis was high in central (84.0%), northern (75.0%) and southern Cross River (69.0%). However, a lower proportion of the vulnerable individuals (26.6%) across the endemic communities were aware of the causes of schistosomiasis. There were significant variations of causes , modes of transmission , ailments , preventions and treatments of perception of urinary schistosomiasis among endemic communities. Schistosomiasis prevalence varies across different communities in the study area and closely associated with water related activities. This high prevalence is sustained by poor awareness of the causes of the disease in endemic communities. Therefore, mass mobilisation and health education is required in the area